Art within Art Evidenced in Artistic Requirements and Production Constraints of Cinema Theatre Industry: A Comparative Study of the Films "Shakespeare in Love" and "Topsy-Turvy" - Al-Majli, Hossam Abdullah (Arts for Linguistic & Literary Studies, 2023)
This study aims to demonstrate how cinema portrayed controversial connection between theatre industry writing requirements and the production/financial demands with reference to the two films: the American film "Shakespeare in Love" and the British film "Topsy-Turvy." The critical analytic film discourse and balanced approach was used. The study is divided into an introduction and four sections, and a conclusion. It overviewed theater production, introduced the two films, discussed their writing and economic aspects, and compared both the films, highlighting the importance of striking balance between artistic freedom and financial stability as well as continuous collaboration and innovation. The study revealed that drama writing during actors' preparations ahead of performance was incomplete. It was also concluded that there was a close interconnectedness between writing (playwright) and economics (financial funding) in the theater industry, that government funding proved significant to prevent theatre industry bankruptcy, and that affirmation of understanding the impact of historical and cultural contexts on writing and economics in the theater industry was essential. The two films under study represented autobiographical accounts of the lives of three individuals who had a significant influence on the British theater: Shakespeare, Gilbert, and Sullivan.